Aligning glocal agendas for international education: Using English-medium education to enhance quality education. Issue 2 (1st October 2021) - Båge, Karin; Gaunt, Albin; Valcke, Jennifer
Abstract : In recent years, there has been growing interest amongst universities around the world on reflecting upon the contribution of higher education to a global society and exploring ways to broaden the curriculum to enable students to make a meaningful contribution to the world (de Wit et al. 2015 ). This paper will suggest that Higher Education Institutions (HEIs) are at the centre of centripetal forces behind global and local agendas, as well as at the centre of centrifugal forces behind English-Medium Education (EME) that have provided friction favourable to enhancing the quality of education and initiate curricular reform at Karolinska Institutet (KI). At the global level, quality education has been defined by the United Nations through the universally adopted Sustainable Development Goals (SDGs), to be one that purposefully includes inclusion, global citizenship, appreciation of cultural diversity and culture's contribution to sustainable development (UNESCO 2017 ). Nationally, the Swedish Ministry of Education's internationalisation inquiry (Bladh et al. 2018) specifically links internationalisation to quality and to the integration of international understanding and intercultural competence in the curriculum. Locally, this has created conditions favourable for HEIs to align new strategic plans with this understanding of quality, bringing internationalisation to the forefront of their education programmes. At the same time, the introduction of EME in HE has acted as a catalyst for transforming pedagogy to support the acquisition of twenty-first-century skills (Coyle 2013 ; Dafouz and Smit 2020 ; Valcke and Wilkinson 2017 ). The question of language in HE, in combination with the necessary adaptation to global agendas, has thus led university teachers to consider the pedagogical, linguistic and cultural implications of their practices as they have never done before. Focusing on KI as a case in point, this paper attempts to address what the convergence of policies, from the global to the local, with classroom practices means for developing quality EME at university.